Knowledge, Attitude of Parents’s and Quality of Life in Children with Chronic Kidney Disease - Van Dem, Pham; Thi Thu Hoai, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 1DO - 10.25073/2588-1132/vnumps.4200, 2020)
Objectives : To identify the percentage of parents having the correct knowledge of caring their children and evaluable quality of life in children with chronic kidney diseases. Subject and method : descriptive cross sectional study and  evaluated the Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Scales of 115 children with chronic kidney diseases (CKD) and their parents who treated at Department of Pediatric of Bach Mai hospital. Results: t he parents’ correct knowledge about CKD was persistant and relapse (90,4% and 89,4%). The sourse of information parents ’ s from medical staffs was 48,2% and 23% from social networking. Over 50% of parents thought that knowledge getting from medical staffs was necessary. Beside that 33% of parents thought that information gettinh from social networking was harmful. Total quality of life score of children with CKD was 21,9 ± 14,9  point. Physical and learning field were more effective. However, total quality of life score of children with CKD whose parents got consulting of medical staffs was lower than wothout medical staffs’s consulting. The difference between total quality of life score of children with CKD and job of parents was not is not statistically significant. Conclusion: the supply more information will help parents understand their role in co-operation with medical staffs to help the children integrate into the normal society and enhance their quality of life. Keywords Knowledge,chronic kidney diseases. References [1] S.F. Chen and M. Chen, Complement Activation in Progression of Chronic Kidney Disease, Adv Exp Med Biol, 1165 (2019) 423-441. [2] M. Robert Kliegman, M.D. Priya Pais and Ellis D.Avner, Nephrotic syndrome, Nelson textbook of pediatrics, edition 19th, (2011). [3] Sách dược lý học lâm sàng, Tác dụng sinh lý và biến chứng của corticoid, Nhà xuất bản Y học, Hà Nội (2003), 596- 604. [4] J.W. Varni, The PedsQ LTM measurement model for the pediatric quality of life inventory [serial online], truy cập ngày 20 tháng 10 năm 2018 tại http://www.pedsql.org/pedsq12.html. [5] Le Thi Ngoc Dung, Ngo Thi Kim Nhung, Tran Pham Dieu, Complications of nephrotic syndrome in Children,s Hospital 2, Ho Chi Minh city Medicine Journal 10 (2006) 31-36. (In Vietnamese). [6] Nguyen Thanh Mai, Nguyen Thu Le, Study quality of life in children with cancer post one year of diagnosis and treatment, resident doctor graduate thesis, Hanoi Medical University, 2011 (In Vietnamese). [7] W. Varni, C.A. Limbers, T.M. Burwinkle, Impaired health- related quality of life in children and adolescents with chronic conditions: a comparative analysis of 10 disease clusters and 33 disease categories severities utilizing the PedsQL TM 4.0 generic core Scales, Health and Quality of Life Outcomes 5 (2007) 43-58.